Analisis Pengaruh Kompetensi Tenaga Kerja terhadap Efektivitas Penggunaan Teknologi Produksi - Azra Bayu Afrianto; Syahru Rifky; Fazri Achmad Nur Fadilah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the effect of workforce competence on the effectiveness of production technology utilization in the manufacturing industry through a quantitative empirical approach with a causal research design. Workforce competence was operationalized through technical operating skills, work experience, and training intensity, while production technology effectiveness was measured using productivity level, production cycle efficiency, and defect rate indicators. Data were collected from production operators working in semi-automated and automated manufacturing systems using structured questionnaires and production documentation. Statistical analysis was conducted using simple linear regression to evaluate the relationship between workforce competence and production technology effectiveness. The findings indicate that workforce competence has a significant positive influence on production productivity, operational stability, process efficiency, and product quality consistency. Operators with higher competence levels demonstrated better adaptability toward industrial technology implementation and machine-based production systems. The study also highlights the strategic importance of competency development, ergonomic work systems, and continuous training programs in strengthening industrial competitiveness and supporting sustainable manufacturing performance within technology-oriented production environments.